2017
DOI: 10.11622/smedj.2017072
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effectiveness of a novel CPRcard™ feedback device during simulated chest compressions by non-healthcare workers

Abstract: RESULTS Overall, the CPRcard group achieved a better median compression rate (CPRcard 117 vs. control 122, p = 0.001) and proportion of compressions within the adequate rate range (CPRcard 83% vs. control 47%, p < 0.001). Compared to the no-card and blinded-card groups, the CPRcard group had a higher proportion of adequate compression rate (CPRcard 88% vs. no-card 46.8%, p = 0.037; CPRcard 73% vs. blinded-card 43%, p = 0.003). Proportion of compressions with adequate depth was similar in all groups (CPRcard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The 2015 AHA Guidelines recommend and the AHA mandated in 2017 use of audiovisual feedback in all CPR training 8 14 31. Previous studies indicate that use of feedback for CPR performance significantly improves CPR quality 16–28. In our study, CPR quality was significantly better in the QCPR Classroom than in the control group.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The 2015 AHA Guidelines recommend and the AHA mandated in 2017 use of audiovisual feedback in all CPR training 8 14 31. Previous studies indicate that use of feedback for CPR performance significantly improves CPR quality 16–28. In our study, CPR quality was significantly better in the QCPR Classroom than in the control group.…”
Section: Discussionsupporting
confidence: 55%
“…We are currently facing a period of transition to CPR training with a feedback device as various feedback devices have been introduced, and research has supported their effectiveness 16–28. However, they are unavailable for CPR training targeting a large population.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information about characteristics and outcomes of included studies are also shown in S2 and S3 Tables in Supplementary materials. Among 42 studies included, 32 were RCTs, 6 studies [18,36,45,54,55,57] were randomized crossover controlled trials and 4 studies [24,48,49,53] were non-randomized studies. There were 13 studies conducted in North America [18,2224,34,35,37,40,44,49,52,53,58], 19 in Europe [17,2527,2931,33,38,39,4143,45,46,48,51,55,57], and 10 in the Asia-Pacific region [1921,28,32,36,47,50,54,56].…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that, with feedback on compression rate from the test device, the rescuer could perform higher quality of CPR with higher compression rate and without compromising compression depth [38]. The other 4 studies also found that real-time feedback devices improved the quality of bystander CPR in a simulation setting [5457].…”
Section: Resultsmentioning
confidence: 99%
“…The CPRcard is a novel, credit card-sized feedback device that provides visual assistance to achieve proper depth and rate of chest compressions. (13) It is part of a research study in collaboration with Laerdal Medical (Norway) to evaluate whether the DARE programme and CPRcard training would bring about a change in the attitude and confidence of the public in saving lives and whether they lead to any improvements in bystander response rates and victim survival. Participants receive a CPRcard at the start of their training and use it during their compression practice.…”
Section: Community Interventionsmentioning
confidence: 99%